2020
DOI: 10.1371/journal.pone.0226936
|View full text |Cite|
|
Sign up to set email alerts
|

Seasonality of ventricular fibrillation at first myocardial infarction and association with viral exposure

Abstract: To investigate seasonality and association of increased enterovirus and influenza activity in the community with ventricular fibrillation (VF) risk during first ST-elevation myocardial infarction (STEMI). MethodsThis study comprised all consecutive patients with first STEMI (n = 4,659; aged 18-80 years) admitted to the invasive catheterization laboratory between 2010-2016, at Copenhagen University Hospital, Rigshospitalet, covering eastern Denmark (2.6 million inhabitants, 45% of the Danish population). Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, data in the literature suggested that SCD may occur as a consequence of a trigger factor in the context of electrical or structural heart disorder (genetic or acquired), which acts as a predisposing condition. Known exogenous triggers resulting in the fatal event of SCD may be fever, alcohol intake, electrolyte disorders, hypertensive crisis, infection, cytotoxic drugs, and pregnancy [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Moreover, regular physical activity is an important exogenous factor affecting the risk of SCD in predisposed subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, data in the literature suggested that SCD may occur as a consequence of a trigger factor in the context of electrical or structural heart disorder (genetic or acquired), which acts as a predisposing condition. Known exogenous triggers resulting in the fatal event of SCD may be fever, alcohol intake, electrolyte disorders, hypertensive crisis, infection, cytotoxic drugs, and pregnancy [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Moreover, regular physical activity is an important exogenous factor affecting the risk of SCD in predisposed subjects.…”
Section: Introductionmentioning
confidence: 99%